ANALYSIS OF TIME INTERVAL BETWEEN BREAST CANCER DIAGNOSIS AND TREATMENT - Formigheri, Alessandra; Brollo, Janaina; Vivian, Fernando; Grochot, Rafael Maciel; Copatti, Solange de Cassia Pezzi; Reiriz, André Borba; Madi, José Mauro; Kneubil, Maximiliano Cassilha (Mastology, 2018)
Introduction: Breast cancer has a good prognosis when treated early. However, the mortality rate in Brazil is still high. The time interval between radiological suspicion and diagnosis/treatment impacts the survival. Methods: This is a retrospective crosssectional study that assessed patients treated at a reference center, with abnormal breast imaging findings and subsequent confirmation of breast cancer, from January 2011 to June 2015. We reviewed variables related to the dates of the abnormal test result, first mastology appointment, biopsy, surgery, and the start of chemotherapy – when indicated. Time intervals were compared using the Friedman and Kruskal-Wallis tests with the software SPSS® 23.0. Results: We analyzed 65 patients. The median time between the abnormal test result and first mastology appointment was 35 days; between first mastology appointment and biopsy, 31 days; between biopsy and surgery, 85 days; and between surgery and chemotherapy, 137 days. The last two intervals showed significant differences (p<0.001). Discussion: Breast cancer patients had a significant delay until surgery and the start of chemotherapy. Early integration of the multidisciplinary team involved in this process and internal audits are necessary to optimize time intervals.